Penyelesaian Wanprestasi Nasabah dalam Perjanjian Gadai Emas di PT Pegadaian Cabang Jemursari - Qur'Anna Savitri Bella Santoso; Anajeng Esri Edhi Mahanani (Yustisia Tirtayasa, 2022)
In dealing with life, humans basically want all their desires to be fulfilled. Moreover, as technology and science advance at an increasing rate in today's times, so does the quality of life of the people. This will result in a greater need for life, which causes people to tend to fulfill their basic needs. However, the COVID-19 pandemic is currently underway, and its effects are being felt by many. Factors such as job loss, lonely work, and restrictions imposed by the government will certainly have a significant impact on people's economic life. In the midst of the COVID-19 pandemic, people continue to think creatively and devise strategies to survive. They don't just sit still. As a result, there are many financial institutions available to help with the problems facing society today. In this case the community is assisted by a Limited Liability Company (PT) Pegadaian (Persero). One company that has an official license to do business in Indonesia is a Limited Liability Company (PT) Pegadaian (Persero) between the customer and the pawning institution. In addition to improving the welfare of the underprivileged and supporting government initiatives in the field of economy and national development, PT. The main purpose of Pegadaian is to help those who need money or funds so that they do not fall into the hands of loan sharks or bondmen who charge relatively high interest rates. The method used is empirical yuridical, using a qualitative descriptive approach. The results of this study indicate that the settlement of default at PT. Pegadaian Jemursari Branch by conducting an auction of the customer's collateral. This has been agreed by the customer if he is unable to pay the collateral installments. Constraints in the settlement are unclear customer data because customers change identities but do not notify the pawnshop, jewelery models that are too old to make old goods to be sold and people are not interested in buying the auctioned goods. The solution in the settlement is to increase the loan amount so that it can pay off the previous loan shortfall, provide a longer loan period, and ask if there are other items that can be guaranteed